Immunohistochemical expression of fibrillin‐1 and fibrillin‐2 during tooth development. (18th December 2014) - Kira‐Tatsuoka, M.; Oka, K.; Tsuruga, E.; Ozaki, M.; Sawa, Y.
Abstract : Background and Objective: Oxytalan fibers are categorized as a microfibril assembly without elastin deposition, and are unique components in the periodontal ligament (PDL). However, little is known about their formation during PDL development. To clarify the mechanisms of oxytalan fiber formation in developing PDL, we performed immunohistochemical analysis to detect the direct expression of fibrillin‐1 and fibrillin‐2, which are major components of microfibrils. Material and Methods: Frozen sections of lower molars from mice at several stages of growth were prepared without chemical fixation and decalcification using the film transfer method. Immunostaining was performed with anti‐fibrillin‐1 and ‐2, and anticytokeratin antibodies. Results: Fibrillin‐1 was not expressed in the dental follicle during the crown forming stage. At postneonatal day 9, fibrillin‐1 expression started with meshwork appearance between the epithelial cells from Hertwig's epithelial root sheath at the root dentin surface. Fibirillin‐2 was detected much earlier than fibrillin‐1 expression. Fibrillin‐2 was expressed with a liner appearance, running parallel to the root axis in PDL, and was partially co‐expressed with cytokeratin 14 expression in Hertwig's epithelial root sheath. Furthermore, we detected both fibrillin‐1 and fibrillin‐2 expression in human PDL. Fibrillin‐1 was detected in fibers with a vertically oriented root axis in PDL. Fibrillin‐2 was widely expressed in PDL, including around the epithelial cell rests of Malassez. Fibrillin‐1 and fibrillin‐2 were clearly co‐expressed in thick fiber structures in human PDL. Conclusion: Our results suggest that both fibrillin‐1 and fibrillin‐2 expression is required to form thick oxytalan fibers in PDL. Based on the expression patterns for fibrillin‐1 and fibrillin‐2, they have different functions during tooth root and PDL development. Early expression of fibrillin‐2 may regulate dental epithelial cell behavior during root and PDL development.